Design and implementation of a glove theater of cardboard materials for the students of the Kindergarten Department (Al-Academy, 2021)
The current research aims to develop the skills of the kindergarten students in designing and implementing a theater for gauntlets made of cardboard materials. To study this, the researcher determined to build teaching plans for design and implementation skills according to (Kolb model).The results of this research showed the effectiveness of teaching plans according to (Kolb's model) in developing skills of design and implementation (theater for gauntlets made of cardboard materials) for the students of the Kindergarten Department - the experimental group. Which had a positive effect to reach the desired results in the design and implementation of the gauntlet theater and dealing with cardboard materials